ANALISIS PROGRAM PENDIDIKAN INKLUSI TERHADAP PARTISIPASI BELAJAR SISWA BERKEBUTUHAN KHUSUS DI SD NEGERI KLAMPOK 01 - Adinda, Suci; Melyana Fitri, Rila; Nurpratiwiningsih , Laelia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study employed a qualitative approach with a case study research design, aiming to describe the inclusive education program implemented to support children with special needs in participating in learning activities at SD Negeri Klampok 01. Based on the findings, it can be concluded that SD Negeri Klampok 01 has implemented an inclusive education program through various efforts tailored to the needs of students with special needs. However, the implementation still faces several challenges, such as the absence of special assistant teachers, limited facilities, and the use of a general curriculum that has not been specifically adapted for students with special needs.